KEPADATAN POPULASI DAN PERTUMBUHAN KERANG DARAH Anadara antiquata L. (Bivalvia: Arcidae) DI TELUK SUNGAI PISANG, KOTA PADANG, SUMATERA BARAT - Nurdin, Jabang; Marusin, Neti; Izmiarti, Izmiarti; Anjas, Anjas (Makara Journal of Science, 2006)
The population density and growth of the cockle Anadara antiquata L. Pelecypoda in Pisang River bay area Padang city, west Sumatera. The research has been done from March to December in 2004. The cockles A. antiquata were collected with systimatic stratified method. The cockle A. antiquata colletion site were divided three strata. The each strata were divided three station based on the water depth. Results of the research showed that the higest density of the cockle A. antiquata was found at station 1 strata III (1.8 ind./m2) and the lowest density at the station 3 strata I (0.9 ind./m2). The higest growth rate of A. antiquata was the length 3 cm (0.064 ± 0.043 cm/ind./15 day) and the lowest growth rate was the length 5 cm (0.009± 0.011 cm/ind./15 day) with corellation similarity Y=0.087–0.0165X; r=0.976).